The Effect of Personality Traits on Subject Choice and Performance in High School: Evidence from an English Cohort - Silvia Mendolia; Ian Walker (Institute for the Study of Labor (IZA), 2014)
This paper investigates the relationship between personality traits in adolescence and performance in high school using a large and recent cohort study. In particular, we investigate the impact of locus of control, self-esteem and work ethics at age 15, on test scores at age 16, and on subject choices and subsequent performance at age 17-18. In particular, individuals with external locus of control or with low levels of self-esteem seem less likely to have good performance in test scores at age 16 and to pursue further studies at 17-18, especially in mathematics or sciences. We use matching methods to control for a rich set of adolescent and family characteristics and we find that personality traits do affect study choices and performance in test scores - particularly in mathematics and science. The results are stronger for adolescents from disadvantaged socio-economic backgrounds. We establish the robustness of our results using the methodology proposed by Altonji et al. (2005) that consists in making hypotheses as to the correlation between the unobservables that determine test scores and subjects' choices and, the unobservables that influence personality.
Keywords: I10; I21; 330; personality; education; locus of control; self-esteem